Korelasi Antara Komunikasi Organisasi dengan Iklim Kerja - Astuti, Astuti; Akram, Akram (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2023)
Â This study aims to: 1) describe the reality of organizational communication; 2) describe the reality of the work climate; and 3) examine the correlation between organizational communication and work climate at Madrasah Tsanawiyah Islamic Middle School 1 Bone south Sulawesi. This research uses quantitative methodology with correlational design to explain the research questions. The instrument used to measure the variabels of this study was a questionnaire then analyzed with descriptive statistics and inferntial statistics use analiysis of the product moment with SPSS version 21 software. The result of the study show in descriptive of organizational communication is in the good category of 83,05% and work climate is in the conducive category of 81,09%. In addition, the analysis of inferential with correlation product moment analysis suggest that there is a positive and significant correlation between organizational communication and work climate, signified by correlation coefficient of 69,4%, which is at strong level of correlation.